Analisis Penggunaan Renolith Dan Fly Ash Terhadap Kuat Tekan Bebas Dan Kuat Geser Pada Tanah Lempung - Joni, Yafettt; Yusuf, Andi Rumpang; Setiawan, Arman (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Clay soil has weak particle bonding and low load-bearing capacity, making it less suitable as a subgrade material in construction. One method to address this issue is stabilization by adding renolith and Fly Ash to the clay soil as stabilizing agents that can bind and fill the soil’s pores. This study aims to evaluate the impact of renolith and Fly Ash on clay soil by testing its unconfined compressive strength and shear strength. The method used involved adding 6% renolith to each sample, with Fly Ash varied at 20%, 25%, and 30%. Mixing was done at the optimum moisture content, obtained from compaction tests. Three samples were prepared for each composition. The unconfined compressive strength of the original soil was 0.597 kg/cm², which increased with the addition of renolith and Fly Ash to 0.637 kg/cm², 0.663 kg/cm², 0.792 kg/cm², and 1.011 kg/cm². The original soil’s shear strength was 0.5835 kg/cm², which rose to 0.6428 kg/cm², 0.9398 kg/cm², 1.0285 kg/cm², and 1.2522 kg/cm² with renolith and Fly Ash. Thus, renolith and Fly Ash effectively enhance the unconfined compressive and shear strength of clay soil.